Cardiac Diastolic Evaluation in Pregnant Women with Abnormal Glucose Tolerance: An Opportunity to Detect the Early and Subclinical Alterations and Prevent Cardiovascular Diseases - B. Pintaudi; G. Di Vieste; F. Corrado; M. F. Creazzo; A. Fazio; A. Valenti; R. D’Anna; A. Di Benedetto (Journal of Diabetes Research)
Objectives of this study were to assess diastolic function in pregnant women with abnormal glucose tolerance (AGT), compared with normal glucose tolerance (NGT) women, and to evaluate the insulin resistance status and its association with Doppler-echocardiographic indexes. Echocardiograms of 108 consecutive Caucasian women with singleton pregnancies were performed. Insulin resistance status was estimated by the homeostasis model assessment of insulin resistance (HOMA-IR) and the quantitative insulin sensitivity check index (QUICKI). All the studied women showed normal diastolic patterns. Patients with AGT (50.9%), as compared with NGT women, had higher HOMA-IR (1.70±1.30 versus 1.01±0.81, P=0.003), lower QUICKI (0.36±0.005 versus 0.40±0.06, P=0.004), higher lateral mitral annulus late diastolic velocity (13.6±4.9 versus 11.9±4.9, P=0.03), and higher A-wave velocity, the wave responsible for the active atrial contraction component (75.2±14.2 versus 67.7±16.2, P=0.01). At multivariate regression analysis HOMA-IR was the only parameter associated with A-wave velocity. In conclusion, women with AGT had an increased subclinical diastolic active participation, which is associated with higher levels of insulin resistance. For the increased risk of deterioration of cardiac diastolic function, earlier and more seriously than normal pregnancy, AGT women may have a careful followup to detect the early signs of cardiac alteration and to prevent cardiovascular diseases.